Analisis Formularium Obat Instalasi Farmasi di Rumah Sakit Umum Royal Prima Medan - Nadiyah Santika; Chrismis Novalinda Ginting; Suci Erawati; Florenly Florenly; Ali Napiah Nasution (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze drug formulations in the pharmaceutical installation at the Royal Prima General Hospital Medan. The method in this research is descriptive qualitative. The results showed that the hospital had prepared formularies, maintained formalities, supervised adherence to formulary use, and proposed formulae in pharmaceutical installations. In conclusion, the hospital has carried out a drug formulary in the pharmaceutical installation. Keywords: Drug Formulary, Pharmacy Installation